2019
DOI: 10.1186/s12913-019-4603-2
|View full text |Cite
|
Sign up to set email alerts
|

Dementia assessment and management in primary care settings: a survey of current provider practices in the United States

Abstract: BackgroundPrimary care providers (PCPs) are typically the first to screen and evaluate patients for neurocognitive disorders (NCDs), including mild cognitive impairment and dementia. However, data on PCP attitudes and evaluation and management practices are sparse. Our objective was to quantify perspectives and behaviors of PCPs and neurologists with respect to NCD evaluation and management.MethodsA cross-sectional survey with 150 PCPs and 50 neurologists in the United States who evaluated more than 10 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
64
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 55 publications
1
64
2
1
Order By: Relevance
“…While almost all reviewed measures reported data on concurrent validity, the estimates for several individual domain subtests within some tools were low. These findings are concerning, particularly when considering the need for a battery to distinguish among different types of MCI and dementia and inform differential diagnoses in non-specialty settings ( 16 ). On the other hand, we found that most measures required minimal involvement of an examiner in test administration and scoring of results and were available as standalone applications on several device types (e.g., PC, tablet computer, etc.).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While almost all reviewed measures reported data on concurrent validity, the estimates for several individual domain subtests within some tools were low. These findings are concerning, particularly when considering the need for a battery to distinguish among different types of MCI and dementia and inform differential diagnoses in non-specialty settings ( 16 ). On the other hand, we found that most measures required minimal involvement of an examiner in test administration and scoring of results and were available as standalone applications on several device types (e.g., PC, tablet computer, etc.).…”
Section: Discussionmentioning
confidence: 99%
“…An additional and important limitation of these conventional tools is that administration, scoring, interpretation, and documentation require substantial clinical staff time. Indeed, among the commonly reported reasons to not conduct the screening were insufficient time during visits and lack of confidence in performing the evaluation ( 7 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite that, the diagnosis of dementia can be delayed by the insidiousness of the symptoms and the perceptions by both patients and GPs/FPs that it may be just a sign of normal aging (7). As many as two-thirds of people with dementia may be misdiagnosed and there is often a significant delay between symptom onset and diagnosis (8). Even in highincome countries with advanced health-care systems, more than half of dementia cases are not formally diagnosed (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Second, our sample included a substantial number of participants with less typical dementia syndromes, including earlier onset and atypical variants of AD. At the same time, this limitation may also be regarded as a strength of the study given a shift towards biological definition of AD and the importance and challenges of identifying its atypical variants in clinical practice [ 3 , 43 ]. Finally, there was a trend for greater CDR Sum of Boxes scores in Aβ+ versus Aβ− participants, and although all analyses controlled for this variable, it is possible that our findings may in part be related to an overall greater a disease severity effect not captured by the CDR.…”
Section: Discussionmentioning
confidence: 99%